2008
DOI: 10.1097/mca.0b013e3283162489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients undergoing enhanced external counterpulsation and spinal cord stimulation for refractory angina pectoris

Abstract: The results from this study show that both EECP and SCS therapy reduce angina in patients with refractory angina pectoris; the response to EECP was slightly more effective than that to SCS. Thus, EECP can be used as an alternative treatment for patients not responding to electrical stimulation. The beneficial effects in the treated groups were maintained during the 12 months follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A significant reduction in angina pectoris was measured by CCS-class in the EECP group compared to the no EECP group. This symptom relief has earlier been demonstrated [30]. The possible mechanisms responsible for the improvement of the angina status include enhancement of the endothelial function, promotion of collateral circulation and improved ventricular function [31].…”
Section: Discussionmentioning
confidence: 73%
“…A significant reduction in angina pectoris was measured by CCS-class in the EECP group compared to the no EECP group. This symptom relief has earlier been demonstrated [30]. The possible mechanisms responsible for the improvement of the angina status include enhancement of the endothelial function, promotion of collateral circulation and improved ventricular function [31].…”
Section: Discussionmentioning
confidence: 73%
“…Finally, changes in CCS classes were observed in 3 trials11,16,23 across all 12 including studies, and the logarithm of OR was used as effect size to assess differences in the proportion of patients having a decrease of 2 or more CCS classes (considered clinically significant). Efficacy comparison between SCS and control was OR 2.12 (1.19 to 3.76) with no heterogeneity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, studies were excluded where patients had a myocardial infarction 6,11. We also excluded studies that had no relevant event in both the treatment or control groups, for the reason that these trials provided no information on the magnitude of the treatment effects.…”
Section: Methodsmentioning
confidence: 99%
“…Despite differences in these and other characteristics, including duration of follow‐up, and also protocols of SCS therapy (e.g., continuous vs. intermittent SCS, as well as stimulation frequency), these observational studies showed consistent results supporting significant beneficial effects of SCS in RAP patients (Table 2) (19,34–48).…”
Section: Observational Studies Of Scs In Rap Patientsmentioning
confidence: 91%